Nursing diagnosis of the Nutrition domain identified among the elderly in the community - Jorge Wilker Bezerra Clares; Maria Célia de Freitas (Universidade Federal de Goias, 2013)
The objective of this descriptive study was to identify the nursing diagnosis under the Nutrition domain, according to NANDA International Taxonomy II, in elderly patients of primary health care units in Fortaleza, Ceará, Brazil. The intentional sample consisted of 52 subjects. Data collection was performed at the elderly's home, in May and June of 2011, by means of the application of a nursing history, following the theoretical framework proposed by Henderson. The nursing diagnoses were established following the stages proposed by Risner. Nine nursing diagnoses were identified among the 14 listed under the Nutrition domain. The main were: Risk for electrolyte imbalance (50%), Risk for deficient fluid volume (50%) and Imbalanced nutrition: less than body requirements (32.7%). These diagnoses can support health/nursing interventions focused on elderly nutrition, aiming to meet the real needs of this group, from a comprehensive and resolving perspective. Descriptors: Aged; Nursing Diagnosis; Elderly Nutrition; Primary Health Care; Nursing.